Sequencing wild and cultivated cassava and related species reveals extensive interspecific hybridization and genetic diversity - Bredeson, Jessen V; Lyons, Jessica B; Prochnik, Simon E; Wu, G Albert; Ha, Cindy M; Edsinger-Gonzales, Eric; Grimwood, Jane; Schmutz, Jeremy; Rabbi, Ismail Y; Egesi, Chiedozie; Nauluvula, Poasa; Lebot, Vincent; et al. (Nature Biotechnology, 2016)
The global genetic diversity of cassava and related Manihot species is revealed by sequencing of 53 cultivated and wild accessions and genotyping of 268 African cassavas, providing a vital resource for breeding. Cassava ( Manihot esculenta ) provides calories and nutrition for more than half a billion people. It was domesticated by native Amazonian peoples through cultivation of the wild progenitor M. esculenta ssp. flabellifolia and is now grown in tropical regions worldwide. Here we provide a high-quality genome assembly for cassava with improved contiguity, linkage, and completeness; almost 97% of genes are anchored to chromosomes. We find that paleotetraploidy in cassava is shared with the related rubber tree Hevea , providing a resource for comparative studies. We also sequence a global collection of 58 Manihot accessions, including cultivated and wild cassava accessions and related species such as Ceará or India rubber ( M. glaziovii ), and genotype 268 African cassava varieties. We find widespread interspecific admixture, and detect the genetic signature of past cassava breeding programs. As a clonally propagated crop, cassava is especially vulnerable to pathogens and abiotic stresses. This genomic resource will inform future genome-enabled breeding efforts to improve this staple crop.